Scientific priorities for the use of alternative energy sources in railway transport - A. B. Kosarev; I. A. Rebrov; S. N. Naumenko; A. V. Barch (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Alternative energy sources, mostly related to “green” energy, are one of the promising trends in the development of energy generation, including for the global railway sector. This is due, firstly, to its desire to preserve its environmental advantages by reducing carbon dioxide emissions into the environment and increasing energy efficiency, and secondly, to a reduction in the use of such sources as oil and coal as fuel resources in the coming decades.In a world where 95 % of motorized vehicles use oil as fuel, the greenhouse gas emissions per passenger-kilometer for rail transport are five times less than for road transport and 20 times less than for air transport. Therefore, one of the key tasks in the development of railway transport is the creation of high-speed highways that will serve as an alternative to road and air communications over short distances.In addition to the well-known alternative energy technologies, the railway transport traditionally conducts scientific research to improve energy-saving technologies, which include the use of excess recuperation energy when rolling stock braking.Also, projects for the use of renewable energy sources — heat pump installations — have proved their effectiveness in railway transport: heating switches from the ground, use of heat from compressors of hill complexes to heat electrical centralization posts and heat transformers of traction substations for its own needs.The role of alternative energy sources in railway transport is constantly growing. The efficiency of using alternative energy sources at the Russian Railways is largely determined by a scientific approach that allows, based on own experience or experience in introducing innovations in related industries, to determine the place, time and degree of their implementation, taking into account technical and technological features of production processes inherent in a particular structural unit companies. Among the innovative technical solutions in railway transport, the most priority ones are solutions aimed at the development of high-speed lines, recuperation systems, as well as heat pump technologies.